2012
DOI: 10.1016/j.taap.2012.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative potency approach based on H2AX assay for estimating the genotoxicity of polycyclic aromatic hydrocarbons

Abstract: a b s t r a c t a r t i c l e i n f oPolycyclic Aromatic Hydrocarbons (PAHs) constitute a family of over one hundred compounds and can generally be found in complex mixtures. PAHs metabolites cause DNA damage which can lead to the development of carcinogenesis. Toxicity assessment of PAH complex mixtures is currently expressed in terms of toxic equivalents, based on Toxicity Equivalent Factors (TEFs). However, the definition of new TEFs for a large number of PAH could overcome some limitations of the current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 45 publications
4
45
0
1
Order By: Relevance
“…It was also reported that micronucleus formation is correlated with H2AX phosphorylation [7] and that ␥H2AX is a reliable biomarker of pre-cancerous cells in vivo [8,9]. These data support the assumption that H2AX phosphorylation could be an appropriate biomarker of genotoxicity, as suggested in recent in vitro and in vivo studies [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…It was also reported that micronucleus formation is correlated with H2AX phosphorylation [7] and that ␥H2AX is a reliable biomarker of pre-cancerous cells in vivo [8,9]. These data support the assumption that H2AX phosphorylation could be an appropriate biomarker of genotoxicity, as suggested in recent in vitro and in vivo studies [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 79%
“…The In Cell Western technique was previously reported to allow the determination of cell viability in parallel to genotoxicity for adherent cells (ACHN, HepG2, LS-174T and SH-SY5Y) [10,11,18,19]. Briefly, after treatment with pesticides, cells were fixed with 4% paraformaldehyde (Electron Microscopy Science) for 20 min for adherent cells.…”
Section: In Cell Western (Icw) Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…More than 30 PAHs have been identified; among them 13 are genotoxic (Audebert, Zeman, Beaudoin, Pery, & Cravedi, 2012;Audebert et al, 2010) or carcinogenic (EFSA, 2008; IARC, 2010b) and they are most probably neurotoxic (Crépeaux et al, 2013;Schroeder, 2010). It should be emphasized that processing procedures, such as smoking, drying, and cooking of food are commonly thought to be the main sources of contamination by PAHs (Scientific Committee on Food, 2002).…”
Section: Process-induced Food Toxicantsmentioning
confidence: 99%
“…The findings that one γH2AX focus corresponds to one double strand break [3,5] and that a broad spectrum of mutagens can induce γH2AX (reviewed in [6]) ensures that γH2AX is a sensitive indicator of DNA damage. In regulatory science, γH2AX is expected to be a useful biomarker of genotoxicity of chemicals [7][8][9][10][11][12] and is also used for detection of genotoxic environmental pollutants such as polyaromatic hydrocarbons and cigarette smoke [13][14][15]. In pharmacology, γH2AX is a good indicator of efficacy of cancer drugs which damage DNA and also may be a potential target of cancer drugs [16,17].…”
Section: Introductionmentioning
confidence: 99%